Decolonizing place in early childhood education - Nxumalo, Fikile, 1971- (New York, NY : Routledge, 2019)
"The volume draws from Nxumalo's sustained engagement with early years research sites and practice in settler colonial contexts. A lively transdisciplinary dialogue is enacted through concrete examples that reconfigure children's messy entanglements with the more than human, including mountains, fallen trees, bees, worms and gardens. Chapters are anchored around new theoretical and methodological frames, such as refiguring presence, geotheorizing, and testifying-witnessing. Each frame is a call to action to meticulously destabilize the damaging logics of settler colonial anthropocentrism. While holding space for the many promises of posthumanist and more-than-human perspectives, Nxumalo confronts their limitations for resolving the persistent Western appropriation of Indigenous world making and place relations. The standout final chapter proposes an ethico-ontological framework for nuanced, contingent alliances among Black and Indigenous pedagogies that tackles questions of (de)coloniality across transits of empire"--
Refiguring presences -- Unsettling forest encounters -- Restorying garden relations -- Geotheorizing place relations -- Living with bee death -- Inhabiting a black anthropocene.
OCLC-licensed vendor bibliographic record.
Keywords: Nature -- Study and teaching (Early childhood); Early childhood education -- Social aspects; Decolonization -- Study and teaching (Early childhood); Culturally relevant pedagogy; EDUCATION / Elementary; EDUCATION / General